The impact of synchronous virtual flipped classroom on EFL students speaking skill - Safrul Muluk; Habiburrahim Habiburrahim; Syarifah Dahliana; Faishal Zakaria; Azizah Azizah; Muhammad Safwan Safrul (Studies in English Language and Education, 2025)
Flipped learning within blended learning has attracted interest for its potential benefits. However, implementing a fully blended model with in-person synchronous learning remains challenging. Therefore, this mixed-methods study investigates a modified flipped approach using a virtual synchronous classroom environment, replacing traditional face-to-face interaction with online instruction. Specifically, our study focused on its implementation in the context of a Public Speaking class, aiming to explore students experiences and levels of learning anxiety with the modified flipped instructional method. A number of 43 out of 50 English major students from one of the state Islamic universities in Indonesia, in their fifth semester, completed and submitted the questionnaires. The results of the study indicated that the implementation of a virtual synchronous flipped classroom had a dual effect, positively influencing both the advancement of students speaking abilities and the alleviation of their anxiety in speaking English. The students found the Synchronous Virtual Flipped Classroom (SVFC) engaging and intellectually stimulating, recommending its adoption via platforms like Zoom and WhatsApp. While they recognized the benefits of technology, their views varied contextually, particularly regarding social interaction. Despite the advantages, students expressed dissatisfaction with the lack of social presence and sensory experience compared to traditional classrooms. Technical issues further hampered peer interaction and impacted their learning experience. These findings provide useful information regarding the potential and limitations of virtual synchronous flipped classrooms in enhancing speaking skills and managing anxiety in language learning.